Edukasi dan Layanan Kesehatan Bagi Staf Guru Di Sekolah Madrasah Aliyah Negeri I Kota Gorontalo - Ischak, Netty Ino; Bambang, Rita; Badu, Ririn; Polontalo, Widya Cahyaningsih; Yusuf, Kartika Endarwaty; Daaliwa, Neva; Lumuru, Feyske Youke; Fitri, Farah Alifia (Damhil: Jurnal Pengabdian kepada Masyarakat, 2025)
Teachers are important pillars in the education process who often face high workloads and psychosocial stress, but their health attention is still minimal. This community service activity aims to provide education and health services for teachers in schools in an effort to improve their quality of life and work productivity. The methods used are health counselling, basic health checks, and personal medical consultations. Evaluation was conducted through pre-test and post-test as well as qualitative feedback. The results showed significant improvements in health knowledge and early detection of health problems among teachers. This program has the potential to be widely replicated as a preventive health strategy for educators